Equality Before the Law in the Investigation of Child Sexual Violence Committed by Community Figures: A Study at Tuban Police - Anita (DE RECHT (Journal of Police and Law Enforcement), 2026)
Child sexual abuse is an inhumane crime. This crime causes prolonged fear and psychological suffering to the victim. The perpetrators can be the people closest to the victim, the school environment, even in the place of the environment of people we respect. The application of the principle of equality before law in the early stages of the legal process is very necessary to be applied because in essence all people deserve the same rights under the umbrella of the law, including children. In investigating and uncovering criminal acts of sexual violence against children committed by community leaders, different characteristics were found. The purpose of this research is to know and understand the problems of investigation in revealing cases of sexual violence against children committed by community leaders and how the application of the principle of equality before the law to the investigation where the perpetrators are community leaders. This research uses empirical legal research methods, namely by obtaining and collecting data in the field (filed research) by conducting interviews. This empirical legal research uses a qualitative type, namely by explaining the reality obtained from cases in the field while trying to reveal things that actually happen. Here the socio-legal problem approach becomes important because it is able to provide a more holistic view of legal phenomena in society. Based on the analysis of the data and facts, it is concluded that the problematic investigation in the crime of sexual violence against children by community leaders in the jurisdiction of Tuban police station is the lack of witnesses, the lack of information that can be extracted from the surrounding community and the lack of investigator personnel, especially women police, especially for handling women and children.